Level of Education and Disability among the Elderly People from Buenos Aires - Malena Monteverde; Enrique Peláez; Dora Celton (Población y Salud en Mesoamérica)
The context in which ageing is occurring in Latin America and the Caribbean countries raises questions about future trajectories in the prevalence of disabilities by age. In this sense, it is of great importance to study the behaviour of the prevalence of disabilities and analyse the risk factors in populations of the region. The aim of this study is to analyse the prevalence of disabilities among the individuals 60 years and over in Buenos Aires and to evaluate the differences between groups with different educational levels. The data used come from the study "Health, Welfare and Aging"-SABE (Spanish acronym)- for Buenos Aires. Based on this information, we estimate the prevalence of disabilities by level of education and we analyse the effects of different risk factors on the likelihood of experiencing disability among individuals with different levels of education. The results suggest that educational level acts as a major protector against the risk of experiencing disabilities in ADL and IADL and the relationship would be partially mediated by health profiles of the individuals.